2002
DOI: 10.1046/j.1365-2222.2002.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric basophil activation test by detection of CD63 expression in patients with immediate‐type reactions to betalactam antibiotics

Abstract: The basophil activation test is a particularly useful technique in the diagnosis of patients with IgE-mediated allergy to betalactams and allows the identification of 50% of patients. Used in conjunction with CAP, it allows the identification of 65.5% of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(194 citation statements)
references
References 18 publications
(25 reference statements)
12
176
2
3
Order By: Relevance
“…The first studies using the basophil activation test to analyze βlactam allergy reported a sensitivity of 50% in patients who tested positive for at least 1 penicillin in a skin test and a specificity of 93%. 59,60 Similar data were obtained in a multicenter study, 61 which re ported a sensitivity of 50% and a specificity be tween 89% and 97%, and emphasized the need to test more than 1 βlactam at a minimum of 2 concentrations to obtain optimal results.…”
Section: Immediate or Immunoglobulin-e-mediated Reac-supporting
confidence: 59%
“…The first studies using the basophil activation test to analyze βlactam allergy reported a sensitivity of 50% in patients who tested positive for at least 1 penicillin in a skin test and a specificity of 93%. 59,60 Similar data were obtained in a multicenter study, 61 which re ported a sensitivity of 50% and a specificity be tween 89% and 97%, and emphasized the need to test more than 1 βlactam at a minimum of 2 concentrations to obtain optimal results.…”
Section: Immediate or Immunoglobulin-e-mediated Reac-supporting
confidence: 59%
“…Activation of basophils in these patients' blood can be measured by flow cytometry targeting the specific basophil markers CD63 or CD203c. Despite specificity of 93.3%, the sensitivity of BAT is only 50% although may be higher for cephalosporins [136,172,173]. In a cohort of 41 amoxicillin-allergic patients, followed up over a 4-year period with both BAT and RAST tests every 6 months, the disappearance of IgE-specific antibody was earlier with BAT than with RAST.…”
Section: Basophil Activation Testmentioning
confidence: 99%
“…For BAT, an optimal threshold>1.97 yields 51.4% sensitivity and 90.3% specificity. A SI>2 as optimal threshold for BAT positivity for antibiotics has been previously described in large multicenter studies, with 50% sensitivity (1,20,21). By comparing the ROC curves performed for R and SI, the area under curve and the sensitivity seems to be lower for BAT when compared to RIA, but the statistical significant difference has not been attained (p=0.11).…”
Section: Figure 2 Box-plot For Si Values (Stimulation Index) For Basmentioning
confidence: 71%